Investigation of ATG16L1 rs2241880 Polymorphism with Cancer Risk: A Meta-Analysis - Abdolkarim Moazeni-Roodi; Farhad Tabasi; Saeid Ghavami; Mohammad Hashemi (Medicina, 2019)
Background and Objectives: Previous studies have investigated the impact of the ATG16L1 rs2241880 (Thr300Ala) polymorphism on individual susceptibility to cancer, but the conclusions are still controversial. To get a more precise evaluation of the correlation between ATG16L1 rs2241880 polymorphism and cancer susceptibility, we performed a meta-analysis of the association of all eligible studies. Materials and Methods: Searches were performed in the Web of Science, PubMed, Scopus and Google Scholar databases up to November 2018. A total of 12 case-control studies from 9 articles comprising 2254 cases and 4974 controls were included. Statistical analysis was achieved by STATA 14.1 and Review Manager 5.3 software. The odds ratios (ORs) with 95% confidence intervals (95% CIs) under five genetic models were used to determine the strength of association among rs2241880 polymorphism and cancer susceptibility. Results: The findings did not support an association between the rs2241880 variant in either the overall study population or the subgroups, based on cancer types and ethnicity in any of the genetic models. As far as we know, our study is the first meta-analysis of the association between rs2241880 polymorphism and cancer risk. Conclusions: In conclusion, the findings of this meta-analysis proposes that the ATG16L1 rs2241880 polymorphism may not play a role in cancer development. Further well-designed studies are necessary to clarify the precise role of the ATG16L1 rs2241880 polymorphism on cancer risk.